An Estimation of Survival and Hazard Rate Functions of Exponential Rayleigh Distribution - Hussein, Lamyaa Khalid; Hussein, Iden Hasan; Rasheed, Huda Abdulla (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
In this paper, we used the maximum likelihood estimation method to find the estimation values ​​for survival and hazard rate functions of the Exponential Rayleigh distribution based on a sample of the real data for lung cancer and stomach cancer obtained from the Iraqi Ministry of Health and Environment, Department of Medical City, Tumor Teaching Hospital, depending on patients' diagnosis records and number of days the patient remains in the hospital until his death.